Formulation and Characterization of Luliconazole Loaded Niosomal Gel - Patidar, Jyoti Bala; Gehalot, Narendra; Joshi, Garvita; Jain, Vikas (Journal of Neonatal Surgery, 2026)
Background: Luliconazole is an effective imidazole antifungal; however, its lipophilicity and poor aqueous solubility can limit topical performance and may require frequent application. Vesicular carriers such as niosomes can improve dermal localization and provide controlled release. Objective: This study aimed to develop luliconazole-loaded niosomes using Span 60 and cholesterol by thin-film hydration, optimize vesicle composition, and incorporate the optimized dispersion into a Carbopol 934 gel for sustained topical delivery Methods: Luliconazole was characterized by organoleptic examination, melting point and UV–Visible spectroscopy (λmax 296 nm), and preformulation studies included solubility profiling and FTIR-based compatibility. Eight niosomal batches (F1–F8) were prepared using chloroform:methanol (2:1) with rotary evaporation, hydration in PBS (pH 7.4), and probe sonication. Vesicle size, PDI and zeta potential were determined by DLS. Entrapment efficiency was evaluated by centrifugation and UV quantification of free drug. The optimized batch was incorporated into Carbopol 934 gel and evaluated for appearance, pH, viscosity, spreadability, drug content, in vitro drug release (Franz/dialysis) and stability Results: Niosomes were obtained in the nanosize range (142.8–218.4 nm) with acceptable PDI (0.198–0.321) and negative zeta potential (−19.6 to −26.5 mV). Entrapment efficiency ranged from 58.32% to 82.34%, with batch F4 showing the best overall characteristics (142.8 ± 2.9 nm, PDI 0.198, −26.5 ± 1.3 mV, 82.34 ± 1.25%). The niosomal gel showed skin-compatible pH (6.01 ± 0.03), pseudoplastic rheology, high drug content (98.64 ± 0.51%) and sustained release compared with plain gel (12 h: 76.30% vs 98.76%). Conclusion: Span 60 niosomal gel provided stable nanosized vesicles, high drug entrapment and sustained release, supporting its potential as an improved topical delivery system for luliconazole.